APLIKASI MARKOV CHAIN UNTUK OPTIMASI INTERVAL WAKTU BRIDGE PREVENTIVE MAINTENANCE - , YUSUF QARADHAWI, Hari Agung Yuniarto, ST., M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A bridge is one of land-base transportation facilities that has important role as a connector between two regions separated by river or sea, so that it is fitting to do planned and scheduled preventive maintenance on bridges.Mistakes in determining interval preventive maintenance on bridges will result in the high level of damage on bridgesâ components. The high level of damage on bridgesâ components will impact directly on the maintenance costs incurred and low level of bridgesâ reliability, thus it is appropiate to determine interval optimum preventive maintenance on bridges to preserve bridgesâ reliability and minimize maintenance costs. There are several methods that is possibly used in determining interval preventive maintenance such as algorithm, genetic, markov chain and sensor using.The method used in this research is markov chain because markov chain can predict componentsâ damages in the future periods, besides that, application requirements of markov chain in reliability system are able to be fulfilled by bridgesâ components damage characteristics. The result of this research is in the form of software that is named BRIPMAC. BRIPMAC is a manifestation of modeloptimization that is developed to determine the interval optimum preventive maintenance on bridges based on markov chain analysis.This research succeeds in building a model to determine interval optimum preventive maintenance on bridges based on markov chain analysis by considering minimum maintenance costs and critical components reliability this research also facilitates this model in the form of software. Software making is done by using MATLAB R2010a software and for the model physical apperance is made using Graphic User Interface (GUI) contained in MATLAB software.The developed software testing was done in Krasak bridge that is one of bridges that is managed by National Road Implementation Unit Daerah Istimewa Yogyakarta Province Region (SATKER PJN DIY). The result of BRIPMAC testing on the case study of Krasak bridge shows 3 critical compontens which are pillar, girder, and abutment. Result analysis that is done by BRIPMAC software determines the interval of regular maintenance Krasak bridge in the year of 2013 is 280 days. After comparing the regular maintenance cost and critical components reliability between interval optimum that is recommended by software and regular maintenance that is set by the government in the year of 2013, the efficiency of the regular maintenance cost is in the amount of 23,44%.Besides that, reliability improvement is resulted in every components in the amount of 6.269% for pillars, 5.247% for girder, and 5.52% for abutment.